2020
DOI: 10.1136/neurintsurg-2020-016564
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a radial long sheath protocol for radial artery spasm reduces access site conversions in neurointerventions

Abstract: BackgroundMany neurointerventionalists have transitioned to transradial access (TRA) as the preferred approach for neurointerventions as studies continue to demonstrate fewer access site complications than transfemoral access. However, radial artery spasm (RAS) remains one of the most commonly cited reasons for access site conversions. We discuss the benefits, techniques, and indications for using the long radial sheath in RAS and present our experience after implementing a protocol for routine use.MethodsA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…During the study period, our institution switched to a radial-first approach, which has been associated with a lower risk of complications compared with traditional femoral access, consequently making MMA embolization safer 19–27. In our study, 65 of the 84 cSDHs (77%) were treated via radial access with no major complications.…”
Section: Discussionmentioning
confidence: 79%
“…During the study period, our institution switched to a radial-first approach, which has been associated with a lower risk of complications compared with traditional femoral access, consequently making MMA embolization safer 19–27. In our study, 65 of the 84 cSDHs (77%) were treated via radial access with no major complications.…”
Section: Discussionmentioning
confidence: 79%
“…Clinical RAS refers to arterial spasm that required an intervention to combat it. 6,7 Right TRA Techniques…”
Section: Inclusion Criteria and Definition Of Variablesmentioning
confidence: 99%
“…If the RAS persists, the standard radial sheath is exchanged for a 23-cm long radial sheath because this has previously been shown to decrease the need for access site conversion. 7 In the event that the RAS prevents advancement of the catheter system, even after placement of a long radial sheath, then conversion to transfemoral access is considered. Figure 1 displays an example of clinically symptomatic RAS that necessitated conversion to femoral access.…”
Section: Measures To Counteract Rasmentioning
confidence: 99%
“…12 The incidence of radial artery spasm can also be decreased by use of a long 23 cm hydrophilic sheath because they protect the full length of the radial artery and diminish repetitive friction forces of the catheter against the vessel wall. 13 Although prevention of radial artery spasm is the preferred approach, once radial artery spasm has been detected, several techniques can be used to relieve spasm including forearm heating with forearm compresses, deepening of sedation or induction of general anesthesia, and administering additional intra-arterial vasodilators. 14 A small randomized controlled trial (RCT) (n=20) showed power injecting normal saline through the sheath (10 mL/s for 10 mL) to induce pressure-mediated vasodilation induces greater radial artery intraluminal diameter acute gain when compared with intra-arterial administration of a combination of nitroglycerin and verapamil, while causing significantly less reduction in blood pressure.…”
Section: Radial Artery Spasmmentioning
confidence: 99%